The association between depression, perceived stress, and sexual function among adults attending primary health care services - Kaplan, Mehmet; Ucar, Mehmet; Yigit, Muhammet Faruk (Bmc, 2025)
Background Sexual function is an integral component of overall well-being and is influenced by both biological and psychosocial factors. While psychological distress is known to affect health outcomes broadly, its specific impact on sexual function among adults attending primary health care services has not been well established. This study aims to examine the relationships between sexual functioning and depression, perceived stress, and sociodemographic variables among adults aged 18-45 who attend primary healthcare services, and to determine whether these psychological variables significantly predict sexual functioning. Methods A descriptive cross-sectional study was conducted between January and March 2025 in five randomly selected family health centres located in T & uuml;rkiye. The study was completed with a total of 573 participants. Data were collected using the Beck Depression Inventory (BDI) to assess levels of depression, the Perceived Stress Scale-10 (PSS-10) to measure perceived stress, and the Arizona Sexual Experiences Scale (ASEX) to evaluate sexual functioning. Statistical analyses included independent samples t-tests, one-way analysis of variance, correlation analyses, and multiple regression analyses to explore relationships between psychological factors and sexual health outcomes. Results Analysis of ASEX scores by sociodemographic characteristics revealed significant differences among both male and female participants (p < 0.01). Correlation analyses showed no significant relationship between ASEX and BDI or PSS-10 scores in men, whereas significant positive correlations were found in women. Regression analyses indicated that BDI and PSS-10 explained only 0.3% of the variance in ASEX scores in men (adjusted R-2 = 0.003; p = 0.09), while their explanatory power was higher in women (adjusted R-2 = 0.114; p < 0.01). Conclusions The results indicate that the psychological variables assessed (depression and perceived stress) predict sexual functioning to a greater extent in women than in men. These findings highlight the importance of considering psychological factors such as depression and stress in the assessment of sexual functioning, particularly among female patients, and underscore the value of integrating such considerations into primary care services. Psychological assessments using tools like the BDI and PSS-10 may contribute to a better understanding of risk factors related to sexual functioning and support more holistic approaches within primary care settings.
Keywords: Sexual Function; Primary Health Care; Depression; Stress; Adult Individuals